The Mediating Role of Value Co-creation on the Relationship between Structural supply Chain Orientation and Marketing Adaptiveness: A Structural Equitation Model - Abdelsalam Adam Hamid; Arafa Gebreel Abu Naseib; Emad aldeen Essa Eshag (International Journal of Supply Chain Management, 2018)
the success of the supply chain depends upon the ability to adjust theinterests of various stakeholders of the supply chain members, which is has become a necessity to maintain a competitive advantage in a dynamic environment. SCO affects not only the single firm performance within the supply chain but also the overall performance of the supply chain.Drawing on RBV this study seek to investigate the mediating effect of value co-creation on the relationship between Structural Supply chain orientation and marketing adaptiveness of industrial firms in sudan. the study collected a data from non probability sample of 180 manufacturing firms, This study applies structural equation modelling (SEM) method for data analysis using The result indicates. That both Cooperative Norms and value co-creation significantly contribute to the marketing adaptiveness , also credibility have significance effect on value co-creation . The finding also suggests that value co-creation partially mediates the relationship between structural supply chain orientation(credibility) and marketing adaptiveness. Moreover industrial firms can more adaptability in marketing by maintaining and developing cooperative norms and participating partners in the process of creating value Key Words: Supply chain orientation, Structural SCO, Value co-creation, marketing adaptiveness